A Multiperiod Model and Experimental Evidence of Independence and “Lowballing”* - SCHATZBERG, JEFFREY W.; SEVCIK, GALEN R. (Contemporary Accounting Research, 1994)
Abstract. Auditors, regulators, and academics are interested in the pricing practice of “lowballing” and its relationship to auditor independence. Several analytical models have examined these issues. However, these theories have gone untested primarily due to a lack of field data concerning important environmental variables. In this study, a multiperiod model of lowballing and independence is developed and tested in laboratory markets via the experimental economics methodology. The study contributes to the literature in two respects. First, it represents one of the first studies providing empirical evidence and theory testing of the relationship between lowballing and independence. Second, the model presents a new rationale for low‐ball pricing and its relationship to auditor independence. Lowballing and impairment of independence, occurring without exogenous transaction costs, are caused by positing cross‐sectional variation in audit cost and quality and an informational advantage that accrues to an incumbent auditor‐client pair regarding future variation in these audit dimensions. The model is operationalized in a multiperiod laboratory market consisting of multiple sellers and buyers. Sixteen markets are conducted to test price and reporting predictions of the model. The markets strongly exhibit lowballing behavior, but the exact price predictions are generally not supported. The markets also support reporting predictions, with sellers deviating from truthful reporting (impairing their independence) only when additional future profits are greater than the additional cost of misreporting. Data availability. The laboratory market data used in this paper are available from the authors upon request.